2017
DOI: 10.1128/genomea.00021-17
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Porphyromonas gingivalis Strain A7A1-28

Abstract: Porphyromonas gingivalis is an oral opportunistic pathogen. Sequenced P. gingivalis laboratory strains display limited diversity in antigens that modulate host responses. Here, we present the genome sequence of A7A1-28, a strain possessing atypical fimbrillin and capsule types, with a single contig of 2,249,024 bp and a G+C content of 48.58%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…One may argue that, as the DNA sequencing technologies are advancing very fast, the problems due to the short read length do not bother us any longer. However, there are still metagenomics experiments currently performed using the ‘old’ sequencers that produce short reads [3, 33]; secondly, it is of scientific importance to analyse the ‘old’ sequencing data with improved methods to draw more biologically meaningful conclusions [15, 28]. There are very large volume of such short reads generated in last decade.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…One may argue that, as the DNA sequencing technologies are advancing very fast, the problems due to the short read length do not bother us any longer. However, there are still metagenomics experiments currently performed using the ‘old’ sequencers that produce short reads [3, 33]; secondly, it is of scientific importance to analyse the ‘old’ sequencing data with improved methods to draw more biologically meaningful conclusions [15, 28]. There are very large volume of such short reads generated in last decade.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Although low sequence divergence within genes encoding catalytic domains of gingipains has been found ( 21 ), P. gingivalis clinical isolates exhibited different rates and distribution of Kgp and arginine-specific gingipain (RgpA and RgpB) activities ( 23 ). Sequencing of several P. gingivalis genomes revealed that the bacterium can exchange chromosomal DNA by specific gene rearrangements and allelic exchange through horizontal gene transfer using natural transformation and conjugation ( 20 , 21 , 44 46 ). Importantly, the spontaneous generation of phenotypically different sub-strains, caused in part by differences in genes encoding hemagglutinin domains of Kgp and HagA, can also occur, resulting in significant attenuation in a mouse virulence model ( 47 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…gingivalis virulence, as can be seen in invasive wild type P . gingivalis (W83) [31], and in ATCC 33277, A7436, 381, TDC60, HG66, A7A1‐28, and the only non‐invasive AJW4 strain [32–36]. However, even strains that share the same genes do not exhibit the same virulence.…”
Section: Introductionmentioning
confidence: 99%